Volume 7: Turbomachinery, Parts A, B, and C 2011
DOI: 10.1115/gt2011-45364
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Passage Flow Features in a Transonic Compressor Rotor With Casing Treatments

Abstract: An experimental investigation on casing treatments in a one-stage transonic compressor is presented. The reference case consists of a radially staggered blisk and six circumferential grooves. Speedlines show that this axisymmetric treatment already provided a substantial increase in operating range with relatively small losses in efficiency. Since the onset of rotating stall in tip-critical high-speed compressors is always linked to the tip-leakage flow and the build-up of blockage within the blade passage. Hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
21
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 4 publications
4
21
0
Order By: Relevance
“…Lim [15] showed that an axial skewed slot had the limitation of stall margin improvement when used in a subsonic axial compressor that exhibited modal-type stall inception. A study by Müller et al [16] showed that although the inception of a typical spike-type stall occurred in the smooth casing of a single-stage transonic axial compressor, a part-span stall gradually developed into a full-span stall when circumferential grooves were employed. Their results also show that the mode-type phenomenon did not take place before the stall occurrence.…”
Section: Introductionmentioning
confidence: 98%
“…Lim [15] showed that an axial skewed slot had the limitation of stall margin improvement when used in a subsonic axial compressor that exhibited modal-type stall inception. A study by Müller et al [16] showed that although the inception of a typical spike-type stall occurred in the smooth casing of a single-stage transonic axial compressor, a part-span stall gradually developed into a full-span stall when circumferential grooves were employed. Their results also show that the mode-type phenomenon did not take place before the stall occurrence.…”
Section: Introductionmentioning
confidence: 98%
“…Many studies to investigate casing treatments in compressors have been reported (Moore et al [1971], Prince et al [1974], Paulon and Dehoudt [1982], Smith and Cumpsty [1985], Fujita and Takata [1985], Lee and Greitzer [1990], Crook et al [1993], Hall et al [1996], Rabe and Hah [2002], Shabbir and Adamczyk [2004], Chen et al [2010], and Mueller et al [2011]). Paulon and Dehoudt [1982] conducted a theoretical investigation of the effects of circumferential-groove casing treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Mueller et al [2007] investigated various circumferential grooves applied to the rotor in a single-stage transonic compressor. Particle Imaging Velocimetry (PIV) was applied to measure the detailed steady flow field near and inside circumferential grooves in an axial transonic compressor stage by Mueller et al [2011].…”
Section: Introductionmentioning
confidence: 99%
“…A variety of casing treatments have been applied to extend the operating range of various compressors (Smith and Cumpsty [1985], Lee and Greitzer [1990], Moore et al [1971], Prince et al [1974], Fujita and Takata [1985], Paulon and Dehoudt [1982], Van de Wyer et al [2010], Chen et al [2010], and Mueller et al [2011]). Most previous experimental studies indicate that casing treatments, which are more effective in delaying stall, tend to induce additional aerodynamic loss at peak efficiency conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the previous studies were aimed at obtaining changes in the overall compressor performance data. Mueller et al [2011] applied Particle Imaging Velocimetry (PIV) to measure detailed steady flow field near and inside circumferential grooves in an axial transonic compressor stage.…”
Section: Introductionmentioning
confidence: 99%